Keragaman Jamur yang Mengkontaminasi Beras dan Jagung di Pasar Tradisional Denpasar - I GUSTI NGURAH BAGUS; DWI WIDANINGSIH; I MADE SUDARMA (Fakultas Pertanian Universitas Udayana, 2017)
The diversity of fungi that contaminate rice and corn in the traditional market of Denpasar. Rice and corn are food commodities consumed daily by the public, but the rice and corn has been contaminated by a fungus, during the process of transportation and storage of experience. So it appears the author wishes to examine how big fungus has contaminated rice and corn in the traditional market town of Denpasar. Research conducted at the Laboratory of Plant Pathology, from April to June 2016. Research carried out consisted of: (1) isolating fungi that contaminate the rice and corn, and identify microscopy morphological, and (2) determine the diversity index and dominance index, as well prevaliensi fungal contamination. Identify the genera level, using reference books Samson et al., 1981; Pitt dan Hocking, 1997; Barnett dan Hunter, 1998; dan Indrawati et al., 1999. The results showed that the fungus can contaminate both the rice and corn in the market Kereneng, Agung, Badung and Ketapaian were Aspergillus flavus, Aspergillus niger and Aspergillus spp. The highest prevalence of fungi that contaminate both the rice and maize are the A. flavus, 73.61 % and 92.96 % respectively. Index of diversity in rice and corn amounting to 0.742 0,302. Index of dominance in rice and maize respectively 0.581 and 0.867. Aflatoxins were found to have not reached the threshold tolerated (20 ppb) is in the rice at 0 ppb, while the largest corn at 2,133 ppb in Kereneng market.